2021
DOI: 10.1088/1555-6611/ac3835
|View full text |Cite
|
Sign up to set email alerts
|

Electron Bernstein wave aided heating of collisional nanocluster plasma by nonlinear interactions of two super-Gaussian laser beams

Abstract: In this present theoretical study, we investigate electron Bernstein wave (EBW) aided collisional nanocluster plasma heating by nonlinear interaction of two super-Gaussian laser beams. The interactions of laser beams electric field profiles with electronic clouds of nanoclusters cause the beat wave. The nonlinear ponderomotive force is generated through the beat wave. There may be good potential to excite the EBW aiding cluster plasma to lead electron heating via cyclotron damping of the Bernstein wave. An ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 55 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Such physical mechanisms can contribute to plasma heating. In References [12][13][14][15] authors reported different mechanisms for EBW excitations in plasma using co-propagating or counter-propagating laser sources in the plasma. These findings explain how the laser-aided excitation of EBW can be useful for plasma heating as well as for tuning the heating rate.…”
Section: Introductionmentioning
confidence: 99%
“…Such physical mechanisms can contribute to plasma heating. In References [12][13][14][15] authors reported different mechanisms for EBW excitations in plasma using co-propagating or counter-propagating laser sources in the plasma. These findings explain how the laser-aided excitation of EBW can be useful for plasma heating as well as for tuning the heating rate.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear interaction of laser beams with plasma as well as nanoclustered plasma is a fascinating research field due to its several applications, such as anomalous absorption [1], parametric decay process [2][3][4][5], harmonic generation [6,7], charged particle acceleration [8,9], terahertz radiation generation [10] electron heating [11][12][13] and soft x-ray generation [14]. Plasma is a good candidate as an interacting medium and promises large current generation via laser interaction.…”
Section: Introductionmentioning
confidence: 99%